China's Japan policy : adjusting to new challenges - Zheng, Yushuo, 1949- (New Jersey : World Scientific Publishing, 2015)
China and Japan are the two most important countries in the Asia-Pacific region. Their economic ties are significant not only because they are the second and third largest economies in today's world, but also because their economic relationship has an important impact on regional economic co-operation and international production chains. China's Japan Policy: Adjusting to New Challenges analyzes the significance of Japan in China's foreign policy framework within the broader context of China's world view, its national objectives, and the Chinese leadership's policy adjustments in response to the changing international and domestic circumstances. It looks at China's Japan policy in recent decades since their normalization of relations in 1972. The book also examines the unique characteristics of the China Japan bilateral relationship, especially the historical legacy, territorial disputes, and the special cultural affinities between the two nations. Readers interested in China and Japan will find this an invaluable reference with detailed insights on international relations and economic developments in the Asia-Pacific region. Readership: Undergraduates, postgraduates, researchers, academics, and policymakers interested in international relations in the Asia-Pacific region. -- Provided by publisher.
Introduction -- The PRC's Japan policy: 1949-1968 -- The foreign policy framework of the PRC after the Cultural Revolution -- The PRC's Japan policy within the context of its analysis of global contradictions: 1968-1972 -- The PRC's united front policy in Japan -- The PRC's demands regarding the normalization of Sino-Japanese relations -- The PRC's Japan policy: Consolidation after normalization of relations - The PRC's Japan policy and its foreign policy framework -- The PRC's Japan policy and the'Four Modernizations' -- The PRC's Japan policy in the 1980s -- The PRC's Japan policy in the Mid-1990s: Adjusting to evolving multipolar world -- The increasingly powerful right-wing forces in Japan: Beijing's perception and response -- The PRC's Japan policy in the 21st century: Seeking stability and improving in uncertainties.
Includes bibliographical references (pages 433-458)
Keywords: China -- Foreign relations -- Japan; Japan -- Foreign relations -- China; China -- Relations -- Japan; Japan -- Relations -- China